Current trends in the incidence of late forms of syphilis in Novosibirsk - Aleksey A. Khryanin; Philipp A. Sukharev (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
The main trends in the incidence of syphilis, including its late forms, are analysed in Novosibirsk in 20132017. It was found that during this period there was a trend to a decrease in the incidence of syphilis in Novosibirsk, but there was an increase in cases of detection of late forms of syphilis, in particular late latent syphilis and neurosyphilis, mainly in men at the age of 40 years and older. A unique clinical case demonstrating the complexity of differential diagnosis of neurosyphilis is also presented.